PUBLIC PRIVATE PARTNERSHIP FOR LEAN SUSTAINABLE DEVELOPMENT IN CONSTRUCTION - Ayman Othman; Alaa Hosny Shaaban El-Gendawy (Journal of Construction Project Management and Innovation)
Sustainability of construction projects has become a major issue facing decision-makers, developers, city and urban planners as well as designers worldwide. Construction projects are characterised with the excessive use of natural resources and consumption of energy, which have a crucial impact on the environment and future generations. This called for the construction industry to adopt the Lean principles as an approach to achieve sustainability objectives. Due to its achievement, partnership between public and private sectors turned into a strategic option to promote sustainability of construction projects. The increasing recognition and apparent success of lean principles called for focusing on utilising the knowledge and skills of project participants to develop sustainable construction through enhancing values and eliminating wastes. This paper aims to investigate the role of public-private partnership (PPP) in applying Lean principles as an approach for sustainable development in construction. A research methodology is developed to accomplish four objectives. Firstly, literature review is used to build a comprehensive background about the research topic including partnership, sustainable development and lean principles. Secondly, case studies are presented to explain the role of partnership in delivering sustainable construction projects. Thirdly, developing a framework to facilitate the creation and implementation of partnership between public and private sector towards lean sustainable development in construction. Finally, summarising research conclusions and recommendations for governmental authorities, construction professionals and further research. Research findings showed that creating a partnership between the public and private sectors could play a significant role towards achieving sustainability in construction through lean principles application.